Two ways that women can use to bring to an end to gender violencia with their partners - Aretio Romero, Mª Antonia (Cuadernos de Trabajo Social, 2021)
Women who are trapped by gender violence have a difficult journey to become aware of their situation and to face up to it until they are able to break with it. It is a complex process full of suffering and heterogeneity in which women go through different stages. The existence of two ways to break up from the violent partner has been identified. One of them is based on positive factors that promote the empowerment of women. The other one is based on negative factors that lead to their exhaustion and destruction. In the process for the breakup and moving on from it the measures that permit the woman’s economic and personal independence are decisive. This discovery reveals the inefficiency of many public measures that try to help women affected by gender violence, so radical changes are necessary. Social work plays a crucial role in accompanying women in their process of coping with, breaking up away from and overcoming gender violence, especially for those women who are more vulnerable.